Ecological drivers and habitat associations of estuarine bivalves - McKeon, C. Seabird (PeerJ, 2015)
Community composition of the infaunal bivalve fauna of the St. Lucie Estuary and southern Indian River Lagoon, eastern Florida was sampled quarterly for 10 years as part of a long-term benthic monitoring program. A total of 38,514 bivalves of 137 taxa were collected and identified. We utilized this data, along with sediment samples and environmental measurements gathered concurrently, to assess the community composition, distribution, and ecological drivers of the infaunal bivalves of this estuary system. Salinity had the strongest influence on bivalve assemblage across the 15 sites, superseding the influences of sediment type, water turbidity, temperature and other environmental parameters. The greatest diversity was found in higher salinity euhaline sites, while the greatest abundance of individual bivalves was found in medium salinity mixohaline sites, the lowest diversity and abundances were found in the low salinity oligohaline sites, demonstrating a strong positive association between salinity and diversity/abundance. Water management decisions for the estuary should incorporate understanding of the role of salinity on bivalve diversity, abundance, and ecosystem function.